(untitled) (Journal of Medical & Health Sciences Review, 2025)
Combating with food insecurity, malnutrition and achieving zero waste for the sustainable environment, there has been a surging interest in exploration of alternative techniques for extracting bioactive compounds derived from plants. Green extraction techniques have demonstrated effectiveness and economic affordability in improving the extraction of different plant derived bioactive compounds. In recent years, emphasis on good health and mental well-being has sparked a rising interest in bioactive compounds in food industries. These bioactive compounds have gained much more popularity due to their numerous health benefits. Due to this reason, the demand for these compounds has also increased, whether it extracted from edible or non-edible sources. This paper examined advanced techniques utilized in the extraction process, with a focus on their effectiveness, and specificity such as ultrasound-assisted extraction (UAE), supercritical fluid extraction (SFE), enzyme assisted extraction (EAE), pulsed electric field (PEF), pressurized liquid extraction (PLE) and microwave-assisted extraction (MAE). The concepts, benefits, and challenges of each technique have examined within the context of extracting bioactive substances, including polyphenols, alkaloids, carotenoids, flavonoids and essential oils. These approaches offered various advantages in terms of enhanced extraction efficiency, low solvent consumption and reduced processing time that would be able to meet the growing demand for sustainable decision-making in industries such as food, and pharmaceuticals. Moreover, the incorporation of green chemistry idealized to reduce the amount of solvents used and energy consumption have been emphasized, demonstrating a sustainable approach for extraction of bioactive compounds from plants. Polyphenols extracted from each technique with the specified plant source and their results have been mentioned. Lastly, this article discussed the present challenges and future recommendations in the field, to promote ongoing innovation and awareness of these methods in improving the extraction of new bioactive compounds from plant resources.